2020
DOI: 10.1097/cm9.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel coronavirus causing severe pneumonia in human: a descriptive study

Abstract: Background: Human infections with zoonotic coronaviruses (CoVs), including severe acute respiratory syndrome (SARS)-CoV and Middle East respiratory syndrome (MERS)-CoV, have raised great public health concern globally. Here, we report a novel batorigin CoV causing severe and fatal pneumonia in humans. Methods: We collected clinical data and bronchoalveolar lavage (BAL) specimens from five patients with severe pneumonia from Jin Yin-tan Hospital of Wuhan, Hubei province, China. Nucleic acids of the BAL were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
1,052
2
79

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,183 publications
(1,145 citation statements)
references
References 23 publications
12
1,052
2
79
Order By: Relevance
“…It was shorter among patients > 70-years old compared with those under the age of 70 [8]. The most common symptoms at onset of COVID-19 illness are fever, cough, and fatigue, while other symptoms include sputum production, headache, haemoptysis, diarrhoea, dyspnoea, and lymphopenia [5,6,8,13]. Clinical features revealed by a chest CT scan presented as pneumonia, however, there were abnormal features such as RNAaemia, acute respiratory distress syndrome, acute cardiac injury, and incidence of grand-glass opacities that led to death [6].…”
Section: Symptomsmentioning
confidence: 92%
See 4 more Smart Citations
“…It was shorter among patients > 70-years old compared with those under the age of 70 [8]. The most common symptoms at onset of COVID-19 illness are fever, cough, and fatigue, while other symptoms include sputum production, headache, haemoptysis, diarrhoea, dyspnoea, and lymphopenia [5,6,8,13]. Clinical features revealed by a chest CT scan presented as pneumonia, however, there were abnormal features such as RNAaemia, acute respiratory distress syndrome, acute cardiac injury, and incidence of grand-glass opacities that led to death [6].…”
Section: Symptomsmentioning
confidence: 92%
“…Ten genome sequences of COVID-19 obtained from a total of nine patients exhibited 99.98% sequence identity [19]. Another study showed there was 99.8-99.9% nucleotide identity in isolates from five patients and the sequence results revealed the presence of a new beta-CoV strain [5]. The genetic sequence of the COVID-19 showed more than 80% identity to SARS-CoV and 50% to the MERS-CoV [5,19], and both SARS-CoV and MERS-CoV originate in bats [24].…”
Section: Phylogenetic Analysismentioning
confidence: 94%
See 3 more Smart Citations